Introduction to the research tools mind map - Ale Ebrahim, N. (Xavier Institute of Management, 2013)
With the increasing use of information and communications technology (ICT), researchers are able to use computer software tools to find, organise, manipulate, analyse, and share relevant information. However, there are hundreds of such tools to select from, for various research-related uses. I have collected over 700 tools that can help researchers do their work efficiently. It is assembled as an interactive Web-based mind map, titled Research Tools, which is updated periodically. Created using the MindMeister software platform, Research Tools provides a convenient interface with zoom in/out, screen drag, and other user-friendly features. Being a mind map, Research Tools consists of a hierarchical set of nodes. It has four main nodes: (1) Searching the literature, (2) Writing a paper, (3) Targeting suitable journals, and (4) Enhancing visibility and impact, and six auxiliary nodes. In the mind map, each parent node has several child nodes associated with it, which can be accessed by clicking on the plus (+) sign. Several free tools can be found in the child nodes. Some paid tools are also included. The four main nodes are described below, listing some tools as examples. In the mind map, a green tick sign indicates my preference for some tools. Users can access the tools by clicking on the arrow sign that appears next to the tool title.